HUBUNGAN GRAVIDA, DUKUNGAN SUAMI, DENGAN PARTISIPASI PEREMPUAN HAMIL DALAM KELAS IBU HAMIL: Array (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2019)
The background of writing this article is based on the results of previous research that several classes of pregnant women have been prepared by the government both at the community health center (Puskesmas) and at the Maternal and Child health Service (posyandu) but it has not been utilized optimally. This is evidenced by the participation of pregnant women in this program is still quite low. This article aims to determine the relationship between husband's support with the participation of pregnant women in the utilization of the class of pregnant women. The method used is a literature study or study results from the results of previous researches. The results show that husband's support has a significant influence. Pregnant women who have the support of their husbands are more likely to take classes in pregnant women than those who are not supported. Based on the analysis, it can be concluded that husband's support will increase the participation of pregnant women in the class of pregnant women. The increment of husband's support for both primi and multi gravida is needed in increasing the participation of pregnant women in the class of pregnant women.